The effect of a portion size intervention on French fries consumption, plate waste, satiety and compensatory caloric intake: an on-campus restaurant experiment - Marie Vermote (Nutrition Journal, 2018)
Abstract Background One of the driving factors of dietary overconsumption throughout the last decennia is the increase of food portion sizes. Larger portions induce higher daily energy intake, so reducing portion size may reduce intake of excess calories. However, real-life studies about the effects of portion size reduction are lacking. Therefore, this study examined the effect of a French fries portion size reduction on French fries consumption, French fries plate waste, satiety and caloric intake during the subsequent afternoon among university students and employees in a Belgian on-campus restaurant setting. Moreover, this study evaluated consumers’ perception about the portion size reduction. Methods The study took place over a two-time (i.e. baseline and intervention week) 4-day period (Tuesday–Friday) in the on-campus restaurant where ±1200 meals are served every day. French fries’ portions were reduced by 20% by replacing the usual porcelain bowl served during the baseline week (±200 g) with smaller volume paper bags during the intervention week (±159 g) in a pre-post real-life experiment. French fries consumption and plate waste were measured in 2056 consumers at baseline and 2175 consumers at intervention. Additionally, interviews were conducted directly after lunch and again between 4 and 6 p.m. on the same day to assess satiety and caloric intake at pre and post in a small subsample of both French fries consumers (n = 19) and non-French fries consumers (n = 14). Post-intervention, the same subsample was interviewed about their perception of the portion size reduction (n = 28). Results Total French fries intake decreased by 9.1%, and total plate waste decreased by 66.4%. No differences were found in satiety or caloric intake between baseline and intervention week among the French fries’ consumers. The majority (n = 24, 86%) of French fries consumers noticed the reduction in portion size during the intervention. Although most participants (n = 19, 68%) perceived the reduced portion size as sufficient, only a minority of participants (n = 9, 32%) indicated post-intervention that they would agree with a permanent implementation. Conclusions Reducing portion size may lead to reduced caloric intake, without changing perceived levels of satiety.